The E-Commerce Customer Loyalty: The Role Of Digital Innovation And Paylater Feature With Experiential Marketing As Intervening - Slamet Heri Winarno (Faculty of Economics and Business, Jenderal Soedirman University, 2026)
The study aims to explain how much the role of experiental marketing as intervening in influencing digital innovation and paylater features on e-commerce customer loyalty in Shoppe customers. Using non-probability sampling method, namely simple random sampling, with 100 samples, and quantitative methods. Data analysis using SEM (Stuctural Equation Modelling) analysis. The results showed that digital innovation and paylater feature variables have a big role in influencing customer loyalty, as well as the paylater feature has a big role in influencing experiential marketing. But on the other hand, digital innovation does not have an impact on building customer experiential marketing, and experiential marketing also does not have a significant effect on customer loyalty. As an intervening experiential marketing, it also does not provide a significant role for digital innovation and the paylater feature in realising customer loyalty. This study also provides suggestions for Shopee in implementing an optimal strategy, namely Shopee can add more attractive features to each of its services so that more customer loyalty will be created.